Implementations of the stability and growth pact and the monetary policy strategy in the EMU - Cecan, Seçil Suner (My University, 2007)
Avrupa Parasal Birliği (APB), ortak bir merkez bankası tarafından idare edilen merkezileştirilmiş bir para politikası ve merkezileştirilmemiş maliye politikaları ile karakterize edilir. Ortak para politikası, Avrupa Merkez Bankası (AMB) tarafından iki ayaklı para politikası stratejisine göre idare edilmektedir. 1992’deki Maastricht Antlaşması ile AMB’nın temel amacı, fiyat istikrarını korumak olarak belirlenmiştir. Ulusal maliye politikaları ise, İstikrar ve Büyüme Paktı (İBP) çerçevesinde mali kurallar ile sınırlandırılmaktadır. İBP, üye ülkelerde mali disiplini sağlamak yoluyla, fiyat istikrarı amacını desteklemek için oluşturulmutur. İBP ve para politkası stratejisi, uygulamalardan doğan problemler nedeniyle revize edilmiş; ancak halen mevcut olan problemler çözülememiştir. Bu tezin amacı, İBP ve para politikası stratejisi uygulamalarını optimum para alanları teorisi çerçevesinde inceleyerek, bu iki yapının APB için uygun olup olmadığını belirlemek, mevcut sorunları ortaya koymak ve bu sorunlara uygun çözümler üretmektir. Bu tez ve bulguları, herhangi bir parasal birlikte, para ve maliye politkalarının nasıl tasarlanması ve uygulanması gerektiğini anlamada yararlı olabilir. Teorik analiz ve geçmiş tecrübeler, mali kurallar ve merkezileştirilmiş bir ortak para politikasının, APB için ve herhangi bir parasal birlik için vazgeçilmez unsurlar olduğunu göstermiştir. İBP ve para politikası stratejisi uygulamaları, APB’de fiyat istikrarını korumada başarılıdır. Ancak, İBP’nin esneklik problemi, İBP ve para politikası stratejisinin açıklık ve kredibilite problemleri çözülmediği sürece, İBP ve para politikası stratejisi, ekonomik durgunluk, işsizlik ve ekonomik farklılık sorunlarına tam olarak cevap veremeyecektir. Bu iki yapı, bu tezdeki öneriler doğrultusunda revize edilmeli ve daha yüksek derecede bir makroekonomik uyum sağlanmalıdır.

The EMU is characterized with a centralized monetary policy conducted by a common central bank and decentralized fiscal policies. The common monetary policy has been conducted by the ECB according to the two-pillar monetary policy strategy. The primary objective of the ECB was defined by the Maastricht Treaty of 1992 as maintenance of price stability. Nevertheless, national fiscal policies are restricted by fiscal rules under the SGP. The SGP was created to support the price stability objective through proving the fiscal discipline in member countries. Both the SGP and monetary policy strategy were revised in recent years due to problems raised from their implementations, but these revisions could not solve current problems. The objective of this dissertation is to investigate implementations of the SGP and the monetary policy strategy in the EMU under the theory of optimum currency areas, to determine whether these frameworks are suitable for the EMU or not, to clarify the problems with the structures of these two frameworks and finally to produce appropriate solutions. This dissertation and its findings may be helpful to understand how fiscal and monetary policies should be designed and implemented in a monetary union. Theoretical analysis and historical experiences prove that fiscal rules and a centralized common monetary policy are indispensable for the EMU and for any monetary union. Implementations of the SGP and the monetary policy strategy have been successful in maintaining price stability within the EMU. However, the SGP and the monetary policy strategy are not fully capable of responding to economic slowdown, unemployment and economic divergence, unless flexibility problem of the SGP and clarity and credibility problems of both the SGP and the monetary policy strategy are solved. In order to make these frameworks more capable of responding to existing economic problems of the euro area economies, further revisions on the basis of the suggestions in this thesis and a higher degree of macroeconomic convergence are necessary.
Keywords: Avrupa Birliği_Mali Politika; Avrupa Birliği_Para Politikası; Avrupa Merkez Bankası